42.1k views
4 votes
W(x) = x2 + 1; Find w(x + 3)

User Wueb
by
4.6k points

1 Answer

6 votes

Given the function w:


\displaystyle \large{w(x) = {x}^(2) + 1 }

Since we want to find w(x+3), the input would be x+3.

Substitute x = x+3 in.


\displaystyle \large{w(x + 3) = {(x + 3)}^(2) + 1 }

Alternate Solution

The answer above works if you want it in vertex form. For this alternate solution, I will convert the function in standard form.

As we know:


\displaystyle \large{ {(x + y)}^(2) = {x}^(2) + 2xy + {y}^(2) }

Therefore:


\displaystyle \large{ {(x + 3)}^(2) = {x}^(2) + 2(x)(3) + {3}^(2) } \\ \displaystyle \large{ {(x + 3)}^(2) = {x}^(2) + 6x+ 9}

Now for function w:


\displaystyle \large{w(x + 3) = {x}^(2) + 6x + 9+ 1 } \\ \displaystyle \large{w(x + 3) = {x}^(2) + 6x + 10}

Hence:

  • The answer is w(x+3) = (x+3)^2+1 for vertex form
  • OR w(x+3) = x^2+6x+10
User Salva Corts
by
5.3k points